(untitled) (Journal of Asian Development Studies, 2025)
Attitudes towards learningand motivation are interconnected: students’ attitudes determine the level of motivation they have to learn a second language. There are Certain factors that influence students’ attitudes towards learning. This study examined the factors influencing Pakistani university students’ attitudes toward learning a second language. This research examined the effects of factors such as "learner’s personality context," "educational context," and "social context" on the attitudes of second language learners. The motivational theory of Gardner and Lambert (1972) was selected as the theoretical foundation, and the questionnaire was adopted from Getie’s (2020) study and adapted for the current study. Data were collected from one hundred university students. The information was then subjected to both quantitative and qualitative analysis. The study’s findings confirm that Pakistani university students’ attitudes towards English are influenced by a combination of instrumental and integrative motivation, with the educationalcontext being the most determining factor. The interrelationships among personality, educational, and social contexts reinforce the idea that attitudes toward L2 learning are shaped by individual, institutional, and interactional social influences. Findings suggest that improving the quality of teaching, classroom dynamics, and curriculum alignment can significantly impact students’ motivation and attitudes towards English. Meanwhile,more support and tolerance for English outside the classroom could also reinforce a positive attitude.